Persepsi Masyarakat Etnis Cina Non-Muslim Terhadap Perbankan Syariah (Studi Masyarakat Kampung Cina Kota Bengkulu) - Rifqi Maycelino, Faishal; adetio Setiawan, Romi; Cahyono, Andi (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2025)
Abstract. This study aims to determine the perception of non-Muslim Chinese ethnic communities towards Islamic banking, especially the community in Kampung Cina, Bengkulu City. The method used is a descriptive qualitative approach with in-depth interview techniques with ten informants. The results of the study indicate that the majority of the community is aware of the existence of Islamic banking and understand that the service is open to all groups. However, their level of understanding of the principles and systems of Islamic banking is still low. This low level of understanding is caused by minimal socialization and limited facilities and services. In addition, most people feel that their financial needs have been met by conventional banks. This study recommends increasing socialization and expanding services to increase the inclusiveness of Islamic banking.